Pengembangan UMKM Melalui Inovasi Serbuk Jamu Tradisional Di Desa Banjaragung, Kecamatan Bareng, Kabupaten Jombang - Ni Putu Kania Devya Prameswari; Acep Samsudin (Jurnal Insan Pengabdian Indonesia, 2023)
The development of MSMEs through traditional herbal medicine powder innovation in Banjaragung Village, Bareng District, Jombang Regency is an activity that helps provide and present the results of a research survey that has been conducted. Innovations in making herbal medicine powder are also rarely found in the village of Banjaragung. Through interviews with traditional herbal medicine MSMEs partners who finally agreed to the innovation and helped carry out the trial to calculate the selling price. With assistance in this training, we are able to expand market reach and improve the economy of traditional herbal medicine MSMEs business actors.